Technology of Large-scale Anti-icing Blades for Low Wind Speed Wind Turbine - HOU Binbin (Kongzhi Yu Xinxi Jishu)
New challenges have been posed for the design of wind power blades due to the features of southern wind farm such as low wind speed and a frozen period of 2 or 3 months every year. Key points of large-scale low wind speed turbine blade design and anti-icing technology have been analyzed and main solutions proposed by domestic and foreign researchers have been reviewed. Analysis of anti-icing technology can be a reference for the design of wind turbine blade in southern wind farm.